Post-Varicella Angiopathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
A 4-year-old male child who presented with right middle cerebral artery (MCA) infarction 2 months after varicella is reported from the University of British Columbia, Children's Hospital, Vancouver, Canada.